IMPROVING THE CONDITION OF THE FOOTHILL ECOSYSTEMS OF KYRGYZSTAN THROUGH THE ACCLIMATIZATION OF NEW TREE AND SHRUB SPECIES (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2022)
The article provides data on the most stable species of tree and shrub plantations,which have been previously introduced in Kyrgyzstan. To improve the vegetation of piedmontecosystems of Chui valley an assortment of tree and shrub species, which are described by botan-ical and floristic and ecological features, is proposed. These species are the most resistant to ad-verse environmental factors and have a decorative appearance. The results obtained are necessaryto reduce the cumulative impact of climate change and the effects of anthropogenic pressure onnatural ecosystems.
Keywords: introduction, acclimatization, foothill ecosystem, trees, shrubs, flora, climate change.